2017
DOI: 10.1108/bfj-06-2016-0290
|View full text |Cite
|
Sign up to set email alerts
|

Are restaurant menus vectors of bacterial cross-contamination? A pilot study in Turkey

Abstract: Purpose The purpose of this paper is to evaluate the hygiene of laminated menus. Design/methodology/approach The cleanliness of 41 laminated menus from first-class restaurant in Ankara, Turkey, was monitored according to the level of bioluminescence measured using a rapid hygiene monitor (Lumitester PD-20 and LuciPac Pen). Aerobic colonies, Escherichia coli, Enterobacteriaceae spp., and Staphylococcus aureus were enumerated. Findings Based on the adenosine triphosphate+adenosine monophosphate hygiene monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…As dining out implies a setting that involves a large number of people in close proximity to one another for an extended period of time, human interaction, and thus risk of infection, is inherent in visiting food service businesses [28]. Further, high-touch surfaces outside the food preparation areas, e.g., restaurant menus, represent a potential risk of cross-contamination [29,30]. Therefore, many consumers did not feel comfortable and were reluctant to revisit restaurants and bars upon reopening [31][32][33].…”
Section: Literature Review and Aimsmentioning
confidence: 99%
“…As dining out implies a setting that involves a large number of people in close proximity to one another for an extended period of time, human interaction, and thus risk of infection, is inherent in visiting food service businesses [28]. Further, high-touch surfaces outside the food preparation areas, e.g., restaurant menus, represent a potential risk of cross-contamination [29,30]. Therefore, many consumers did not feel comfortable and were reluctant to revisit restaurants and bars upon reopening [31][32][33].…”
Section: Literature Review and Aimsmentioning
confidence: 99%
“…Conversely, a lack of cleanliness in a restaurant might be associated with cross-contamination from dirty surfaces leading consumers to think about the food safety risks from eating in that restaurant (Liu and Lee, 2018). These surfaces can even be outside the food preparation areas and may include the dining room, so it is important to have cleaning protocols in place for these areas as well (Bilici et al , 2016). Some areas of the restaurant including furniture, equipment and menus may not be cleaned regularly (Choi et al , 2014), and these surfaces represent a high risk for cross-contamination (Leon and Albrecht, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cross-contaminations can occur at any time during consumers’ dining experiences from the moment they step into the restaurant to the moment they leave the restaurant. For example, some studies have found a high level of contamination on restaurant menus (Bilici et al , 2016; Sirsat et al , 2013). In addition to service equipment, tables, cleaning cloths and menus could lead to bacterial contamination and transfer during the dining experience (Choi et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 87% of menus were found harboring bacteria, including E. coli, which were not further serotyped, and Staphylococcus aureus, both indicating poor hygienic practices, in monitoring studies (8,19,31,81), suggesting that menus should be either cleaned and sanitized or periodically discarded as part of restaurants' hygiene protocol. Laminated menus could easily be added to a restaurants cleaning regimen by simply sanitizing the menus after each customer; paper menus cannot be cleaned as easily but do have a lower moisture content, as previously stated, which suggests they could potentially be used multiple times before discarding them becomes necessary.…”
Section: Atypical Cross-contamination Surfacesmentioning
confidence: 99%